USE OF PROPRANOL FOR TREATING COMPLICATED HEMANGIOMAS IN CHILDREN - Yu. I. Kucherov; Yu. V. Zhirkova; M. G. Rekhviashvili; I. A. Mikhalev; L. N. Moskvitina; D. L. Shiporev (Union of pediatricians of Russia, 2014)
Infantile hemangiomas (IHs) are the most common tumors detectable in infants, including 5-10% of the neonates. Despite the spontaneous involution characteristic of the uncomplicated course of the disease, IHs require therapy in order to prevent disfigurement, functional disorders and cankering. Effective experience of treating IHs with non-selective-blocker propranol was described in 2008. More than 200 articles on effectiveness and safety of -blockers for IH treatment and assessment of potential side effects have been published since then. The article presents published data on the assessment of effectiveness of treating difficult to access hemangiomas with propranol on the basis of the applicable standards of medical care rendering. Special attention is given to the side effects induced by administration of this drug. According to the results of the published scientific works, -blockers appear to be rather effective for IH treatment and feature a high safety profile. However, it is necessary to continue clinical research and establish a sufficient evidence basis in order to definitively confirm this hypothesis.